PEMBIAYAAN MURABAHAH, MUSYARAKAH, MUDHARABAH, IJRAH DAN ITISHNA’ PENGARUHNYA TERHADAP PROFITABILITAS 4 BANK UMUM SYARIAH DI INDONESIA - Indriyani, Indriyani; Mohklas, Mohklas (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
The purpose of this study was to find out whether Mudharabah, Musyarakah, Mudharabah, Ijrah and Itishna ' have an effect on profitability in 4 Islamic Commercial Banks. The population in this study were quarterly financial reports at Islamic Commercial Banks using the Purposive Sampling technique and 64 sample samples were obtained. For the independent variable (X) of this study are Mudharabah, Musyarakah, Mudharabah, Ijrah and Itishna ', while the dependent variable is Profitability. The method used in this study is a quantitative method and the data source is secondary data using multiple regression analysis and hypothesis testing. Partially, Murabaha has a significant effect on profitability. As well as Musyarakah, Mudharabah, Ijrah and Itishna have no effect on profitability.Keywords: mudharabah, musyarakah, mudharabah, ijrah and itishna ', and profitability.